1998
DOI: 10.1007/s000110050338
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on anti-inflammatory activity of phycocyanin in some animal models of inflammation

Abstract: Phycocyanin shows anti-inflammatory activity in four experimental models of inflammation. Its antioxidative and oxygen free radical scavenging properties may contribute, at least in part, to its anti-inflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(101 citation statements)
references
References 14 publications
5
90
0
2
Order By: Relevance
“…Rats treated with either the selected ketorolac tromethamine ODT formula (G5) or Fam® tablets prolonged the tail flick reaction time of the animals and demonstrated significant antinociceptive action (P< 0.05: statistically significant from the control) as shown in table (1). There was no significant differences between the prepared KT fast dissolving tablets and Fam® tablets (P > 0.05 = 0.263).…”
Section: Results and Discusionmentioning
confidence: 95%
See 1 more Smart Citation
“…Rats treated with either the selected ketorolac tromethamine ODT formula (G5) or Fam® tablets prolonged the tail flick reaction time of the animals and demonstrated significant antinociceptive action (P< 0.05: statistically significant from the control) as shown in table (1). There was no significant differences between the prepared KT fast dissolving tablets and Fam® tablets (P > 0.05 = 0.263).…”
Section: Results and Discusionmentioning
confidence: 95%
“…Also, such models can estimate the anti-inflammatory effectiveness of different active substances (1) . Rat paw edema is one of these models in which a suspension of carrageenan is injected into the paw (2) or pleural cavity of the rat.…”
Section: Introductionmentioning
confidence: 99%
“…Antinociceptive and anti-inflammatory properties have been attributed to species of Arthrospira cyanobacteria (such as Arthrospira maxima and Arthrospira platensis), 8,9 due to their naturally high concentrations of phycocyanin, phenolic compounds, and carotenoids. 10,11 Lipid extracts of several species of blue-green algae were shown to decrease the nuclear translocation of nuclear factor-κB, thus contributing to decreased expression and secretion of proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…The primary component of ACE is phycocyanin, which is known to act as an antioxidant and a selective COX-2 inhibitor 13 with documented anti-inflammatory properties. [8][9][10] In addition to phycocyanin, ACE contains antiinflammatory compounds different from phycocyanin yet with complementary anti-inflammatory properties. 25 The purpose of the two clinical pilot studies reported here was to provide evidence for resolution of chronic pain during consumption of a phycocyanin-enriched extract of Arthrospira, known to possess synergistic anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Beta-D-glukan (BDG), mantarlarda, mayada ve kepekte bulunan dallanmış bir glukoz polimeridir. BDG'ların temel immünofarmakolojik aktiviteleri; konağın viral, bakteriyel, fungal ve parazitik enfeksiyonlara karşı direncini güçlendirmesi, retiküloendotelyal sistemin fagositik ve proliferatif aktivitesini artırmasını kapsamaktadır [7][8][9][10] . Bu çalışmada, splenektomi yapılan sıçanlarda, sepsisli hastalardan elde edilen kapsüllü invazif S.pneumoniae serotip 19F'in indüklediği sepsis üzerine, seftriaksonun ve bir immünomodülatör olan BDG'ın tekli ve kombine etkilerinin araştırılması amaçlanmıştır.…”
Section: Introductionunclassified